Market segmentation - a fundamental concept of marketing - McDonald, Malcolm (Henry Stewart Talks, 2008)
Market segmentation, Non cumulative diffusion pattern, The product life cycle, Approximate market shape, Personalizing segments, Market dynamics, Product/market life cycle and market characteristics, Key elements of world class marketing, The market segmentation process, Market mapping, Market definition and segmentation, Micro-segments, Market segmentation and corporate responsibility, Understanding market segmentation
Reviewed at 2016/12/29